introduction to fatwa, shariah supervision & governance in islamic finance - ahcene lahsasna (cert, 2011)
this book aims to provide a sound foundation of knowledge in fatwa and shari'ah governance in islamic finance. this foundation is coupled with very important aspects of islamic jurispendence, legal maxims, and islamic law of contracts.